Cryptococcal-related Mortality Despite Fluconazole Preemptive Treatment in a Cryptococcal Antigen Screen-and-Treat Program. (8th June 2019) - Wake, Rachel M; Govender, Nelesh P; Omar, Tanvier; Nel, Carolina; Mazanderani, Ahmad Haeri; Karat, Aaron S; Ismail, Nazir A; Tiemessen, Caroline T; Jarvis, Joseph N; Harrison, Thomas S
Abstract: Background: Cryptococcal antigen (CrAg) screening and treatment with preemptive fluconazole reduces the incidence of clinically evident cryptococcal meningitis in individuals living with advanced human immunodeficiency virus (HIV) disease. However, mortality remains higher in CrAg-positive than in CrAg-negative patients with similar CD4+ T-lymphocyte counts. Methods: We conducted a cohort study to investigate causes of morbidity and mortality during 6 months of follow-up among asymptomatic CrAg-positive and CrAg-negative (ratio of 1:2) patients living with HIV with CD4 counts <100 cells/µL attending 2 hospitals in Johannesburg, South Africa. When possible, minimally invasive autopsy (MIA) was performed on participants who died. Results: Sixty-seven CrAg-positive and 134 CrAg-negative patients were enrolled. Death occurred in 17/67 (25%) CrAg-positive and 12/134 (9%) CrAg-negative participants (hazard ratio for death, adjusted for CD4 count, 3.0; 95% confidence interval, 1.4–6.7; P = .006). Cryptococcal disease was an immediate or contributing cause of death in 12/17 (71%) CrAg-positive participants. Postmortem cryptococcal meningitis and pulmonary cryptococcosis were identified at MIA in all 4 CrAg-positive participants, 3 of whom had negative cerebrospinal fluid CrAg tests from lumbar punctures (LPs) at the time of CrAg screening. Conclusions: Cryptococcal disease was an important cause of mortality among asymptomatic CrAg-positive participants despite LPs to identify and treat those with subclinical cryptococcal meningitis and preemptive fluconazole for those without meningitis. Thorough investigation for cryptococcal disease with LPs and blood cultures, prompt ART initiation, and more intensive antifungals may reduce mortality among asymptomatic CrAg-positive patients identified through screening. Abstract : Asymptomatic cryptococcal antigenemia was a risk factor for mortality despite a screen-and-treat program with preemptive fluconazole treatment. Cryptococcal disease was a significant cause of death on the basis of clinical and autopsy evidence. Fluconazole monotherapy may be inadequate preemptive treatment.